Longitudinal associations between adolescent psychotic experiences and depressive symptoms. - Sarah A Sullivan; Nicola Wiles; Daphne Kounali; Glyn Lewis; Jon Heron; Mary Cannon; Liam Mahedy; Peter B Jones; Jan Stochl; Stan Zammit (PLoS ONE)
Background Psychotic experiences are prevalent in community samples and are highly correlated with depressive symptoms. This study aimed to investigate the longitudinal associations between psychotic experiences and depressive symptoms between adolescence and young adulthood. Method Prospective cohort study with a 6 year follow-up in a community sample of 7632 adolescents and young adults. Depressive symptoms were assessed with the Short Moods and Feelings Questionnaire and psychotic experiences with a semi-structured clinical interview at 12 and 18 years. Longitudinal and cross-sectional associations were investigated with regression and structural equation models. Results Depressive symptoms and psychotic experiences were associated at each time-point (12 years r = 0.486 [95% CI 0.457, 0.515]; 18 years r = 0.286 [95% CI 0.233, 0.339]) and there were longitudinal within-phenotype associations (depressive symptoms r = 0.252 [95% CI 0.205, 0.299]; psychotic experiences r = 0.662 [95% CI 0.595, 0.729]). There was an across-phenotype association between psychotic experiences at 12 and depressive symptoms at 18 r = 0.139 [95% CI 0.086, 0.192; p<0.001], but no association between depressive symptoms at 12 and psychotic experiences at 18 r = -0.022 [95% CI -0.032, 0.077; p = 0.891]. Conclusions Longitudinal across-phenotype associations were substantially weaker than cross-sectional associations or within-phenotype longitudinal associations. Whilst psychotic experiences at 12 years were associated with a small increase in depression at 18 years, depression at 12 years was not associated with psychotic experiences at 18 years once across-phenotype cross-sectional and within-phenotype longitudinal associations were accounted for. This suggests that the biological mechanisms underlying depression at this age do not increase subsequent risk of psychotic experiences once they resolve.